The Role of Autophagy in Glaucomatous Optic Neuropathy - Adornetto, Annagrazia; Parisi, Vincenzo; Morrone, Luigi Antonio; Corasaniti, Maria Tiziana; Bagetta, Giacinto; Tonin, Paolo; Russo, Rossella (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a conserved lysosomal-dependent pathway responsible for the degradation of cytoplasmic macromolecules. Based on the mechanism of cargo delivery to lysosomes, mammalian cells can undergo micro, macro and chaperone-mediated autophagy. Other than physiological turnover of proteins and organelles, autophagy regulates cellular adaptation to different metabolic states and stressful conditions by allowing cellular survival or, when overactivated, participating to cell death. Due to their structure and function, neurons are highly dependent on autophagy efficiency and dysfunction of the pathway has been associated with neurodegenerative disorders. Glaucomatous optic neuropathies, a leading cause of blindness, are characterized by the progressive loss of a selective population of retinal neurons, i.e. the retinal ganglion cells (RGCs). Here we review the current literature on the role of autophagy in the pathogenic process that leads to the degeneration of RGC in various experimental models of glaucoma exploring the modulation of the pathway as potential therapeutic intervention.